Incorporating Recycled Crumb Rubber into Asphalt: A Comprehensive Review (Journal of Engineering, 2024)
Using asphalt mixtures with added materials became a significant field for enhancing asphalt properties. Crumb rubber or recycled tire rubber is one of these materials that gained great attention because it provides asphalt mixtures with enhanced properties and with the privilege of being economically and environmentally efficient where it reduces the waste tires from being disposed to nature. This study explores the latest articles in this field with a focus on different methods used to incorporate crumb rubber (CR) into the asphalt matrix. It has been noticed that most articles focus on the wet process for incorporating CR into asphalt. This method is known for its efficiency, but it consumes less CR as compared to the dry process. The dry process deals with CR as a substitute rather than an additive, but it is used less around the world in enhancing asphalt properties where it has less effect on asphalt characteristics development. The third method (terminal) is a mix between the mentioned methods and comprises the prospectives of both methods. The need for this research is underscored by the growing environmental and economic challenges associated with waste tire disposal and the continual degradation of road infrastructure. This study contributes to developing more sustainable, durable, and cost-effective road paving solutions by exploring the efficacy and methods of crumb rubber integration into asphalt.